Bertrand competition in markets with network effects and switching costs - Irina Suleymanova; Christian Wey (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2011)
We analyze Bertrand duopoly competition in markets with network effects and consumer switching costs. Depending on the ratio of switching costs to network effects, our modelerates four different market patterns: monopolization and market sharing which can be either monotone or alternating. A critical mass effect, where one firm becomes the monopolist for sure only occurs for intermediate values of the ratio, whereas for large switching costs market sharing is the unique equilibrium. For large network effcts both monopoly and market sharing equilibria exist. Our welfare analysis reveals a fundamental conflict between maximization of consumer surplus and social welfare when network effects are large. We also analyze firms' incentives for compatibility and we examine how market outcomes are affected by the switching costs, market expansion, and cost asymmetries. Finally, in a dynamic extension of our model, we show how competition depends on agents' discount factors.
Keywords: L13; D43; L41; 330; Network Effects; Switching Costs; Bertrand Competition; Duopoly; Product differentiation; Network externalities; Standardization; Competition; Market structure; Dynamic equilibrium